2018
DOI: 10.1038/s41598-018-24001-1
|View full text |Cite
|
Sign up to set email alerts
|

Greater mindful eating practice is associated with better reversal learning

Abstract: Mindfulness-based interventions are thought to reduce compulsive behavior such as overeating by promoting behavioral flexibility. Here the main aim was to provide support for mindfulness-mediated improvements in reversal learning, a direct measure of behavioral flexibility. We investigated whether an 8-week mindful eating intervention improved outcome-based reversal learning relative to an educational cooking (i.e., active control) intervention in a non-clinical population. Sixty-five healthy participants with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…The work of health personnel is characterized by high psychological and emotional demands and a high level of perceived stress [3]. So the promotion of self-care and wellbeing of these professionals through strategies such as practicing mindfulness, become fundamental in maintaining optimum patient care [4][5][6].…”
Section: The Importance Of Mindfulness In Nursing Workmentioning
confidence: 99%
“…The work of health personnel is characterized by high psychological and emotional demands and a high level of perceived stress [3]. So the promotion of self-care and wellbeing of these professionals through strategies such as practicing mindfulness, become fundamental in maintaining optimum patient care [4][5][6].…”
Section: The Importance Of Mindfulness In Nursing Workmentioning
confidence: 99%
“…The participants that were included in the current sample ( n = 58; see Table 1 for group characteristics) largely overlap with those from the sample reported previously ( 28 ). Only right-handed adults in the age between 18 and 55 years old, with a BMI between 19 and 35 kg/m 2 , who had an adequate demand of the Dutch language (i.e., who could understand the task instructions, questionnaires, and intervention materials) and who, importantly, were highly motivated to change their eating behavior (not to lose weight per se ) were included in the study.…”
Section: Methodsmentioning
confidence: 93%
“…Participants also performed a food Stroop task inside the scanner, followed by a reversal learning and outcome devaluation task outside the scanner. Data from these three experimental paradigms are reported elsewhere ( 28 , 40 , 41 ).…”
Section: Methodsmentioning
confidence: 99%
“…More specifically, we found that spending more time on ME behaviours improved independent awareness and increased behavioural flexibility after consistent practice. Behavioural change is associated with behavioural flexibility and stress reduction (Janssen et al , 2018). This flexibility creates the ability to shift and adjust strategies when faced with unexpected situations.…”
Section: Discussionmentioning
confidence: 99%